2011
DOI: 10.1128/iai.01348-10
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of the Prevalence, Maintenance, and IgA Response to Species of the Order Bacteroidales in the Human Gut

Abstract: Bacteroidales species are the most abundant Gram-negative bacteria of the human intestinal microbiota. These bacteria evolved to synthesize numerous capsular polysaccharides (PS) that are subject to phase variation. In Bacteroides fragilis, PS synthesis is regulated so that only one of the eight PS biosynthesis loci is transcribed at a time in each bacterium. To determine if the bacteria evolved this unusual property to evade a host IgA response, we directly studied the human fecal ecosystem. We performed a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 36 publications
5
94
0
Order By: Relevance
“…Consistent with the inflammatory potential of ETBF in the colon, limited studies to date suggest an association with active inflammatory bowel disease (29,30). Further definition of the epidemiology of ETBF was provided by a detailed study by Zitomersky et al, who studied the frequency with which B. fragilis was detected in serial stool samples examined over the course of a year in 15 adults (14). She and her colleagues found that 87% of adults were colonized with B. fragilis and, among these, 46% had fecal ETBF, confirming and extending observations regarding asymptomatic colonization with ETBF in adults.…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 97%
See 1 more Smart Citation
“…Consistent with the inflammatory potential of ETBF in the colon, limited studies to date suggest an association with active inflammatory bowel disease (29,30). Further definition of the epidemiology of ETBF was provided by a detailed study by Zitomersky et al, who studied the frequency with which B. fragilis was detected in serial stool samples examined over the course of a year in 15 adults (14). She and her colleagues found that 87% of adults were colonized with B. fragilis and, among these, 46% had fecal ETBF, confirming and extending observations regarding asymptomatic colonization with ETBF in adults.…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 97%
“…First, B. fragilis possess the most diverse surface polysaccharide gene repertoire of any known bacterium with the ability to synthesize up to 8 distinct capsular polysaccharides (A-H) that likely populate the surface of B. fragilis one at a time (13). The benefit to the organism of its ability to "change its coat" remains unknown, given a single longitudinal human study suggesting that humans tend to be stably colonized with B. fragilis populations expressing a range of polysaccharide types (14). Second, immunologic studies support B. fragilis as a symbiont with the remarkable capacity to modulate homeostatic mucosal immunity as well as contribute to systemic immune development, effects mediated by PSA (15)(16)(17).…”
Section: Bft: a Molecular Link To Colonic Inflammation And Oncogenesismentioning
confidence: 99%
“…Intestinal Bacteroidales species are the most abundant Gram-negative bacteria of the human colonic microbiota, reaching densities of more than 10 10 bacteria per gram of feces (45). Intestinal Bacteroidales species encode an extensive number of proteins dedicated to the synthesis of glycosylated molecules, including many capsular polysaccharides (27), glycoproteins (17), extracellular polysaccharides (11), and glycosylated S-layer proteins (15).…”
mentioning
confidence: 99%
“…In the human gut, the most common gram-negative bacteria belong to the Bacteroidales order, with more than 30 different species producing a large number of phase-variable capsular polysaccharides. In one study, no evidence was obtained for an intestinal IgA driving this variability (Zitomersky et al, 2011). Thus, rather than affecting the intestinal microbiota by causing immune evasion, it seemed that the impact of a mucosal IgA response was mainly immune exclusion of the commensals.…”
Section: Generation Of Specific and Cross-reactive Iga Antibodies To mentioning
confidence: 96%